The emergence of private higher education (PHE) in Ghana: an assessment of the internal quality assurance mechanisms in private universities in Ghana - Odjidja, Josephine (2021)
“An astonishing academic transformation has taken place in Ghana in the last three decades, evidenced by the infiltration of private sector ownership in the higher education sector.”